E-Service Quality, Islamic Service, and Branding in Building Customer Loyalty of Islamic Banks - Nurudin; Muyassarah; Zuliana Rahma; Maltuf Fitri (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Customer satisfaction and loyalty are essential for the success of Islamic banks in Indonesia, particularly as customer expectations grow and competition intensifies. While previous research has explored the impact of service quality and brand experience on loyalty, the results have been inconsistent. This study examines the influence of e-service quality, Islamic service quality, and Islamic branding experience on customer satisfaction and loyalty, while also analyzing the mediating role of satisfaction. Using a quantitative explanatory approach, data were collected from 200 purposively selected Islamic bank customers who had actively used e-banking services for at least six months. The data were gathered through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS software. The findings show that all three independent variables significantly and positively affect customer satisfaction. Moreover, customer satisfaction acts as a significant mediator between these variables and customer loyalty. Among the predictors, Islamic branding experience plays a key role by fostering emotional bonds through values such as honesty, transparency, and trust. This study contributes to the Islamic marketing literature by emphasizing the importance of integrating Islamic values into service and branding strategies to enhance satisfaction and cultivate long-term customer loyalty.